METHODOLOGY FOR THE DEVELOPMENT OF PROFESSIONAL PEDAGOGICAL TRAINING: USING THE EXAMPLE OF TRAINING FUTURE TEACHERS (Journal of Universal Science Research, 2024)
In this article, the author analyzed the current problems, shortcomings and inconsistencies in the process of training qualified personnel in the pedagogical field. Having studied the work of foreign and domestic researchers, he tried to reveal the professional training of the teacher and the requirements for him, as well as the principles of organizing the modern educational process.